2014
DOI: 10.3892/mmr.2014.2153
|View full text |Cite
|
Sign up to set email alerts
|

Saikosaponin-d inhibits proliferation of DU145 human prostate cancer cells by inducing apoptosis and arresting the cell cycle at G0/G1 phase

Abstract: Saikosaponin‑d (SSd), a triterpene saponin compound derived from Bupleurum radix, has been shown to have a cytotoxic effect on various cancer cell lines. However, its effect on prostate cancer cells has remained unexplored. The present study reports the apoptosis‑inducing effect of SSd on the DU145 human prostate carcinoma cell line. Treatment with SSd inhibited DU145 cell proliferation in a concentration‑dependent manner. Flow cytometric analysis showed that SSd inhibited the proliferation of DU145 cells by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“… 2014a, 2014b ; Yao et al. 2014 ), activates caspases apoptosis pathway, including the activation of caspases-3 and caspases-7 (Chiang et al. 2003 ; Chou et al.…”
Section: Ssdmentioning
confidence: 99%
See 2 more Smart Citations
“… 2014a, 2014b ; Yao et al. 2014 ), activates caspases apoptosis pathway, including the activation of caspases-3 and caspases-7 (Chiang et al. 2003 ; Chou et al.…”
Section: Ssdmentioning
confidence: 99%
“… 2014a, 2014b ; Yao et al. 2014 ), suppresses the expression of COX-2, which has been shown to be involved in carcinogenesis (Lu et al. 2012b ; He et al.…”
Section: Ssdmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical intervention can do some help to early stage RCC only, while patients with advanced tumor are still in urgent need for more promising approaches. Although studies have proved that SSd can inhibit cell growth and induce apoptosis in malignancies such as liver cancer, prostate cancer and thyroid carcinoma [8,23,24], its effect in RCC remains unclear. Our study is the first to explore the role and mechanism of SSd in RCC treatment which has been proved in this research to be able to inhibit RCC cell growth in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…SSd has also been found to inhibit cell growth of human lung cancer A549 cells and human hepatoma HepG2 and Hep3B cells by induction of p53/p21mediated G1 phase cell cycle arrest and activation of Fas/FasL apoptotic signaling pathway (Hsu et al, 2004). Recent studies further demonstrated that downregulation of CDK2/cyclin D1 and P53/P21mediated cell cycle arrest at G0/G1 phase decrease the potential of mitochondrial membrane, and release of cytochrome c are critical for SSd-induced inhibition of human prostate cancer Du145 cells growth and apoptosis of human undifferentiated thyroid carcinoma cells (Yao et al, 2014;Liu and Li, 2014). Several studies also indicated that SSd mediates the apoptosis of human colon cancer HT29 cells via regulation of TRAIL, TRAIL-R, caspase-10 and caspase-8 signaling (Lu et al, 2013).…”
Section: Effects Of Sss On Cancersmentioning
confidence: 99%